Good as gold eaudiobook - Mlynowski, Sarah (Whatever After, 2021)
The fourteenth book in the New York Times and USA Today bestselling series featuring fractured fairy tales for fearless kids! Guess where we are this time? The magic mirror has sent me and my brother, Jonah (plus our puppy, Prince), into the story of Goldilocks and the Three Bears . Fun! There's porridge to taste, chairs to sit on, and beds to nap in. But Goldilocks is in a LOT of trouble, and if we can't help her, we might get stuck here forever! Now we have to: - Skateboard down a mountain - Convince the bear family NOT to eat us - Get one hundred gold coins - Escape the royal jail ...And find the one fairy tale character who can turn straw into gold... Wait... Rumpelstiltskin? What are YOU doing here?!